THE HUBUNGAN ANTARA POSTUR TUBUH TERHADAP KESEIMBANGAN STATIK PADA LANSIA - Lingga Yogi Prasetya; Ari Wibawa; I Nyoman Adi Putrawan (Majalah Ilmiah Fisioterapi Indonesia, 2015)
This study conducted to find the relationship between static posture towards balance in the elderly. This research is a cross sectional study conducted in May 2014 where the population of this study was resident population at Panti Tresna Werda Wana Seraya in Denpasar - Bali. Sampling technique is Non-Probability Sampling, the sample size taken using census sampling technique (saturated), in this case the sample taken 30 of 10 men and 20 women. The results of the study by using the chi-square test analysis, of the 20 people posture with kyphosis obtained 15 static balance with open eyes is categorized as poor and 17 people static balance with closed eyes is categorized as poor. While 10 people with no postural kyphosis obatained 2 people static balance with open and closed eyes is categorized as poor. The value of static balance posture with open eyes p = 0.013 (p <0.05) and static balance posture with closed eyes p = 0.001 (p <0.05). The risk of poor static balance with open and closed eyes on kyphosis posture 12 times greater (open eyes) and 22.6 times greater (closed eyes) compared with no postural kyphosis which means there is a significant relationship between body posture against static balance in the elderly.